Problematic Alcohol Use in Pokhara, Nepal as Assessed by CAGE Questionnaire - Lamichhane, N; Thapa, DK; Timsina, RR; Shrestha, LV; Sharma, R; Subedi, A. (Journal of Psychiatrists’ Association of Nepal, 2019)
Introduction: Nepal is known to be a hub for alcohol lovers. There is no restriction in sales despite efforts by the government of Nepal. Homemade alcohol is another major problem in the country. Although production and sale has legal policy it is far from being regulated. There has been no survey to assess the extent of problematic alcohol use in the Pokhara Municipality. This was conducted with the Objectives of i) assessing prevalence of problematic alcohol use in the community of a different Wards in Pokhara Metropolitan city and ii) To correlate this with various socio-demographic characteristics. Material And Method: The CAGE questionnaire was administered to all adult individuals above 20 years of age, in houses selected as convenience sampling in different wards of Pokhara Metropolitan city from Jan 2017 to Dec 2017. Nursing students in the community visit were trained and instructed to fill the preformed questionnaire as per the inclusion criteria after taking the consent. Individuals who were not currently undergoing treatment for alcohol use disorders were only included. Results: Among 136 adults who were included in this study, the prevalence of problematic alcohol use was found to be 64.7% (CAGE ≥2). The extent of current alcohol use (n. 124, 91.2 %,) and problematic alcohol use (n. 82, 66.12%) were significantly high (P-value: 0.0001). Conclusion: The prevalence of problematic alcohol use is too high in Pokhara, a tourist destination in Western Nepal. There is an urgent need to formulate a policy for alcohol use in the community taking into account the findings of this study. The distinction of traditional sanction of alcohol users and non users did not apply to this study. Problematic alcohol use was significantly high with no treatment initiate.